Double-strand break repair in the absence of RAD51 in yeast: a possible role for break-induced DNA replication. - Malkova, A (1996)
In wild-type diploid cells of Saccharomyces cerevisiae, an HO endonuclease-induced double-strand break (DSB) at the MAT locus can be efficiently repaired by gene conversion using the homologous chromosome sequences. Repair of the broken chromosome was nearly eliminated in rad52delta diploids; 99% lost the broken chromosome. However, in rad51delta diploids, the broken chromosomes were repaired approximately 35% of the time. None of these repair events were simple gene conversions or gene conversions with an associated crossover, instead, they created diploids homozygous for the MAT locus and all markers in the 100-kb region distal to the site of the DSB. In rad51delta diploids, the broken chromosome can apparently be inherited for several generations, as many of these repair events are found as sectored colonies, with one part being repaired and the other part being lost the broken chromosome. Similar events occur in about 2% of wild-type cells. We propose that a broken chromosome end can invade a homologous template in the absence of RAD51 and initiate DNA replication that may extend to the telomere, 100 or more kb away. Such break-induced replication appears to be similar to recombination-initiated replication in bacteria.